Is there a religious factor in health? - Levin, Jeffrey S. (Journal of religion and health, 1987)
This paper reviews epidemiologic studies employing religion as an independent construct, and finds that most epidemiologists have an extremely limited appreciation of religion. After a historical overview of empirical religion and health research, some theoretical considerations are offered, followed by clarification of several operational and methodological issues. Next, well over 200 studies are reviewed from nine health-related areas: cardiovascular disease, hypertension and stroke, colitis and enteritis, general health status, general mortality, cancer of the uterine corpus and cervix, all other non-uterine cancers, morbidity and mortality in the clergy, and cancer in India. Finally, an agenda for further research is proposed.